Focus cardiac ultrasound core curriculum and core syllabus of the European Association of Cardiovascular Imaging. (26th February 2018) - Neskovic, Aleksandar N; Skinner, Henry; Price, Susanna; Via, Gabriele; De Hert, Stefan; Stankovic, Ivan; Galderisi, Maurizio; Donal, Erwan; Muraru, Denisa; Sloth, Erik; Gargani, Luna; Cardim, Nuno; et al.
Abstract: There is a growing trend of using ultrasound examination of the heart as a first-line diagnostic tool for initial patient evaluation in acute settings. Focus cardiac ultrasound (FoCUS) is a standardized but restricted cardiac ultrasound examination that may be undertaken by a range of medical professionals with diverse backgrounds. The intention of this core curriculum and syllabus is to define a unifying framework for educational and training processes/programmes that should result in competence in FoCUS for various medical professionals dealing with diagnostics and treatment of cardiovascular emergencies. The European Association of Cardiovascular Imaging prepared this document in close cooperation with representatives of the European Society of Anaesthesiology, the European Association of Cardiothoracic Anaesthesiology, the Acute Cardiovascular Care Association of the European Society of Cardiology and the World Interactive Network Focused On Critical Ultrasound. It aims to provide the key principles and represents a guide for teaching and training of FoCUS. We offer this document to the emergency and critical care community as a reference outline for teaching materials and courses related to FoCUS, for promoting teamwork and encouraging the development of the field.